Pengaruh Word Of Mouth Dan Kualitas Produk Terhadap Kepuasan Pelanggan Melalui Keputusan Pembelian di Bakmie Demie SCBD - Chintya Ramadhanti; Rivera Pantro Sukma (CV. ULIL ALBAB CORP, 2023)
The research conducted by this researcher aims to determine and prove the effect of word-of-mouth and product quality on customer satisfaction through purchasing decisions at Bakmie Demie SCBD. The population in this study are Bakmie Demie SCBD customers. The sampling technique used purposive sampling, with a total of 136 respondents. Methods of data collection by distributing questionnaires to respondents. The hypothesis is tested using path analysis with the help of SmartPLS 3.0. The findings from this study indicate that there is no statistically significant direct impact of word of mouth on product quality. However, word-of-mouth does have a positive and significant influence on purchasing decisions. Furthermore, product quality has a positive and significant effect on purchasing decisions. In addition, purchasing decisions have a positive and significant effect on customer satisfaction. Regarding the indirect effect, word-of-mouth has an insignificant impact on customer satisfaction through its influence on purchasing decisions. Likewise, product quality has a positive and significant effect on purchasing decisions through its impact on customer satisfaction. The coefficient of determination for customer satisfaction is 79.7%, for purchasing decisions the coefficient of determination is 85.1%.